Integration of 150 nm gate length N-polar GaN MIS-HEMT devices with all-around diamond for device-level cooling - Rohith Soman; Mohamadali Malakoutian; Jeong-kyu Kim; Emre Akso; Nirupam Hatui; Christian Wurm; Umesh Mishra; Srabanti Chowdhury (Applied Physics Express)
We report the successful integration of low-temperature polycrystalline all-around diamond as heat spreaders with 150 nm gate length N-polar GaN MISHEMT platform to improve power efficiencies for X-band applications. With an all-around integration scheme, the CVD-grown diamond reduces channel’s peak temperature, improving device performance and reliability. A combination of optimized low-temperature diamond growth at 500 °C with the thermally stable molybdenum gate metal and MOCVD-grown SiN _x gate-dielectric was utilized for the successful integration. The fabricated device exhibited a I _DSS of 0.96 A mm ^−1 and an ON-to-OFF ratio of 10 ^5 . This marks the first post-process diamond integration on a RF GaN HEMT device.